Adaptive textile‐reinforced composites: Modeling and application. Issue 1 (December 2014) - Linse, Thomas; Ulbricht, Volker; Kluge, Axel; Cherif, Chokri
Abstract The scope of the present paper is the modeling of the mechanical behavior of textile‐reinforced composites with an integrated system of wires made of shape memory alloys. A phenomenological model for the description of the material behavior of shape memory alloys is implemented in a commercial FE code. As the textile reinforcement shows periodically repeating patterns, the inner architecture of the composite can described by a representative volume element. Effective viscoelastic material parameters of the textile‐reinforced composite are determined with the help of homogenization techniques. For the application of the developed composite structure as a simple actuator, numerical results are compared with experimental data. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)